Cross-resistance profile of the novel integrase inhibitor Dolutegravir (S/GSK1349572) using clonal viral variants selected in patients failing raltegravir - Canducci, Filippo; Ceresola, Elisa R; Boeri, Enzo; Spagnuolo, Vincenzo; Cossarini, Francesca; Castagna, Antonella; Lazzarin, Adriano; Clementi, Massimo (The Journal of infectious diseases, 2011)
Novel integrase inhibitors are in advanced clinical development, and cross-resistance data are needed to consider the possibility to plan a sequential usage within this class of antiretroviral drugs. Ex vivo phenotypic assays were conducted on 11 wild-type and 27 fully replicating recombinant viruses obtained from 11 patients failing previous raltegravir-containing regimens. Dolutegravir maintained its activity in vitro on viruses with mutations in position 143 and 155. However, viruses with mutation Q148R associated with secondary mutations and the combination Q148H+G140S were instead associated with a reduced level of susceptibility to dolutegravir in vitro.